Mesoscale Simulations of the Rheology of Filled Styrene–Butadiene Compounds. Issue 5 (24th May 2018) - Fitzgerald, Barry W.; den Otter, Wouter K.; Luding, Stefan; Briels, Wim J.
Abstract: The ability of a highly coarse‐grained polymer model is explored to simulate the impact of carbon black (CB) filler concentration on the rheological properties of unvulcanized styrene–butadiene melts—an intermediate stage in the production of styrene–butadiene rubber (SBR) commonly used in tyres. Responsive particle dynamics (RaPiD), previously used to study dilute polymeric systems, models entire polymers as single particles interacting through a combination of conservative interactions and transient entanglement‐mimicking forces. The simulation parameters are tuned to the linear rheology of the unfilled melt, as measured using a rubber process analyzer (RPA). For the filled compounds, only the interaction between the polymers and fillers is varied. On top of excluded volume interactions, a slight attraction (≈0.1 k B T ) between polymers and fillers is required to attain agreement with RPA measurements. The physical origins of the small strength of this interaction are discussed. This method offers potential for future numerical investigations of filled melts. Abstract : The impact of carbon black filler on the rheological properties of unvulcanized styrene–butadiene (SB) melts is explored using experiments and simulations. Parameters are tuned to recover the linear rheology of unfilled melts that have been measured using a rubber process analyzer. Inclusion of a slight polymer‐filler attractive potential in simulations is shown to be sufficient to attain qualitative agreement with experiments.